2019
DOI: 10.1111/jpi.12627
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin enhances mitochondrial biogenesis and protects against rotenone‐induced mitochondrial deficiency in early porcine embryos

Abstract: Melatonin, a major hormone of the pineal gland, exerts many beneficial effects on mitochondria. Several studies have shown that melatonin can protect against toxin‐induced oocyte quality impairment during maturation. However, there is little information regarding the beneficial effects of melatonin on toxin‐exposed early embryos, and the mechanisms underlying such effects have not been determined. Rotenone, a chemical widely used in agriculture, induces mitochondrial toxicity, therefore, damaging the reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 58 publications
7
50
2
Order By: Relevance
“…Under physiological conditions, fusion and fission are balanced, and mitochondrial networks are present. Fusion facilitates distribution of metabolites, proteins, and mtDNA and helps maintain electrical and biochemical connectivity [156][157][158]. However, there is little evidence available to describe the precise role played by mitochondrial fusion in microvascular I/R injury.…”
Section: Mitochondrial Fusionmentioning
confidence: 99%
“…Under physiological conditions, fusion and fission are balanced, and mitochondrial networks are present. Fusion facilitates distribution of metabolites, proteins, and mtDNA and helps maintain electrical and biochemical connectivity [156][157][158]. However, there is little evidence available to describe the precise role played by mitochondrial fusion in microvascular I/R injury.…”
Section: Mitochondrial Fusionmentioning
confidence: 99%
“…25 Interestingly, recent studies have shown that melatonin exerts biological effects via a SIRT1-dependent mechanism in aging, inflammation, and embryo development. [26][27][28] Although evidence linking melatonin to the role of SIRT1 has been reported, only a few of the molecular mechanisms involved have been addressed. It would be interesting to clarify the functional link between SIRT1 and melatonin in response to PA-induced lipotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, SIRT1 has been shown to deacetylate and inactivate p53 in response to DNA damage 25 . Interestingly, recent studies have shown that melatonin exerts biological effects via a SIRT1‐dependent mechanism in aging, inflammation, and embryo development 26‐28 . Although evidence linking melatonin to the role of SIRT1 has been reported, only a few of the molecular mechanisms involved have been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our results further demonstrated that mitochondrial dysfunction might be related to the disruption of mitochondrial biogenesis, which involves the synthesis of nuclear‐encoded proteins, and the replication of mitochondrial DNA. PGC‐1α/NRF1/TFAM is currently recognized as the major pathway for regulation of mitochondrial biogenesis (Niu et al, 2020). We found that high‐dose Mn treatment significantly reduced their transcription and expression levels along with an inhibition of mtDNA replication, but that low‐dose Mn treatment increased mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of researches reveal that RSV is a potent activator of sirtuin 1 (SIRT1), which exerts important biological effects on mitochondrial biogenesis by regulating SIRT1’s downstream target genes, such as peroxisome proliferator‐activated receptor gamma co‐activator‐1α (PGC‐1α) (Fanibunda et al., 2019; Wang et al., 2019). PGC‐1α is a central regulator of mitochondrial biogenesis, and mitochondrial DNA is activated and up‐regulated by the transcription factors nuclear respiratory factor (NRF 1) and mitochondrial transcription factor A (TFAM) (Niu, Zhou, Nie, Shin, & Cui, 2020). However, it is not known whether the protective role of RSV is further associated with the activation of the SIRT1/PGC‐1α pathway in Mn‐induced mitochondrial damage.…”
Section: Introductionmentioning
confidence: 99%